High Precision Height Control for Wing-in-Ground Crafts - Yihan Mei; Shanfei Su; Xiaowen Shan; Peng Yu; Hao Wang (International Journal of Aerospace Engineering)
The wing-in-ground effect craft (WIG craft) is a kind of vehicle that flies close to the ground to achieve a flight with low aerodynamic drag and high lift. A robust and precise height control system is essential to ensure small WIG crafts fly safely in ground effect. In this paper, the performance of different high precision height control systems based on PID controllers is investigated numerically with different altitude disturbances. The results show that a control system that operates throttle, elevators, and flaps to control the altitude of the aircraft (TPF control system) results in the minimum overshoot, undershoot, rising tine, and settling time recovering from a disturbed altitude, with fluctuation in pitch angle. Compared to the TPF control system, even though the control system that operates throttle and flaps (TF control system) has a longer settling time and a higher overshoot, it has a smaller oscillation in pitch angle during a disturbed altitude. In addition, operating the throttle helps reduce the change of flight velocity during altitude disturbance. Furthermore, simulation results based on the TPF control system, show that the ground effect has little influence on the performance of control systems.